Influences of geometric and dynamic synchronous errors onto machined surface in 5-axis machining center - Shogo HASEGAWA; Ryuta SATO; Keiichi SHIRASE (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2016)
Unexpected glitches typically occur on the finished surface machined by the 5-axis machining centers, because of geometric and dynamic synchronous errors of the machine. In this study, actual ball-nosed end milling tests of hemispheres and its finished surface simulations with different geometric errors and different position loop gain of feed drive systems were carried out, in order to clarify the influence of the geometric and dynamic synchronous errors onto machined surface. As the results, it is clarified that the influence of geometric errors onto the machined surface is depending on the relationships between the movement of the axes and the surface geometry. In addition, the dynamic synchronous error also influences the machined surface when the velocity of translational and rotary axes changed rapidly.